Rhyme Patterns in Surah Al-‘Ādiyāt: A Stylistic Analysis of Phonological Structure and Qur’anic Linguistic Aesthetics - Laili, Nur; Hakimi, Muhammad Yusuf (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study aims to analyze the rhyme patterns in Surah Al-‘Adiyat through a stylistic approach, focusing on the phonological and aesthetic aspects of the Qur’anic language. The method employed is descriptive qualitative, using text analysis techniques to identify rhyme patterns at the end of verses, sound repetitions such as assonance and alliteration, and their relationship to the structure of meaning within each verse. The findings reveal that Surah Al‘Adiyat exhibits a relatively consistent rhyme pattern, particularly characterized by the dominance of long vowel sounds at the end of verses, which creates a strong, harmonious, and profound rhythm. These sound patterns not only establish phonological cohesion between verses but also enhance the dynamic, firm, and intense impression of the divine message. In addition to serving as an aesthetic linguistic element, the rhyme in this surah plays an important role in emphasizing the meaning of oaths (qasam) in the opening verses and reinforcing the moral and spiritual messages in the subsequent verses. Therefore, this stylistic study demonstrates that the phonological structure of the Qur’an not only contributes to linguistic beauty but also plays a significant role in constructing meaning, deepening readers’ understanding, and strengthening the persuasive power of the text.